Distribution of citrus greening disease in Marathwada region of Maharashtra - SHYAM SINGH, A.K. DAS and (Indian Phytopathology, 2002)
The results of a survey conducted during July 1988 in some 50 citrus (sweet orange cv. Mosambi) orchards in 7 districts of Marathwada, Maharashtra, India, are reported. Symptomatological and biological indexing evidence is presented, which confirmsthe presence of greening disease (Candidatus liberobacter asiaticum) in Marathwada. In greenhouse trials, budwood taken from trees of all ages suspected to be infected with the disease was grafted onto uninfected trees, and the grafted trees were monitored for symptoms at 20-30oC. Results of disease scoring indicated that greening was present in samples from all localities surveyed, with symptoms developing 90-129 days after grafting. The identity of the disease was confirmed by microscopic techniques.